Aerobic photoreactivity of synthetic eumelanins and pheomelanins: generation of singlet oxygen and superoxide anion. (23rd September 2016) - Szewczyk, Grzegorz; Zadlo, Andrzej; Sarna, Michal; Ito, Shosuke; Wakamatsu, Kazumasa; Sarna, Tadeusz
Summary: In this work, we examined photoreactivity of synthetic eumelanins, formed by autooxidation of DOPA, or enzymatic oxidation of 5, 6‐dihydroxyindole‐2‐carboxylic acid and synthetic pheomelanins obtained by enzymatic oxidation of 5‐ S ‐cysteinyldopa or 1:1 mixture of DOPA and cysteine. Electron paramagnetic resonance oximetry and spin trapping were used to measure oxygen consumption and formation of superoxide anion induced by irradiation of melanin with blue light, and time‐resolved near‐infrared luminescence was employed to determine the photoformation of singlet oxygen between 300 and 600 nm. Both superoxide anion and singlet oxygen were photogenerated by the synthetic melanins albeit with different efficiency. At 450‐nm, quantum yield of singlet oxygen was very low (~10 −4 ) but it strongly increased in the UV region. The melanins quenched singlet oxygen efficiently, indicating that photogeneration and quenching of singlet oxygen may play an important role in aerobic photochemistry of melanin pigments and could contribute to their photodegradation and photoaging.